Citrus Diseases Exotic to Florida: Phaeoramularia Fruit and Leaf Spot (PFLS) - Kuang-Ren Chung; Lavern W. Timmer (EDIS, 2007)
PP-234, a 3-page illustrated fact sheet by K.-R. Chung and L. W. Timmer, is part of the Citrus Diseases Exotic to Florida series, which aims to provide a basis for evaluating exotic pathogens that may pose potential risks to Florida citrus and create a decision-making framework to prevent their introduction and spread. It answers several questions, including why it is a concern, causal agent, affected cultivars, typical symptoms, how it is spread, and means of detection and control. Includes references. Published by the UF Department of Plant Pathology, February 2007.